The evidence base for generational differences: where do we go from here? - Parry, Emma; Urwin, P. (Oxford University Press, 2017)
Interest in generational diversity has exploded since the turn of the 21st century. While many researchers are supportive of the concept of generations, a growing number have questioned the validity of the idea that people are different according to when they were born. In this article, we review recent work in the area and build on our own previous studies; which have been highly critical of extant empirical work. Many studies utilize cross-sectional data that do not allow investigation of generational difference; and even when appropriate data are used, the apriori assumption of 4 or 5 generational categories invalidates research findings. We present selected results from analyses we have undertaken to overcome these issues, and identify a more robust direction for the research. Essentially, the theoretical foundation for generational research has some validity, but the existence of generational differences has not been validly tested. We suggest that researchers must investigate whether any cohort-specific differences in attitudes are apparent, and where, if at all, these can be “cut” to identify distinct “structural breaks” between generations. Only by building a body of knowledge, across different social, and economic phenomena will we obtain a true picture of where generational differences lie.